Effect of Banana Peel and Tomato Compost on the Growth of Oil Palm Seeds (Elaeis guineensis Jacq.) Prenursery Stage - Mira Ariyanti; Nadiyanti Nadiyanti; Mochamad Arief Soleh (Jurnal Ilmu Pertanian Indonesia, 2025)
Continuous use of inorganic fertilizers that do not follow Good Agricultural Practices causes soil damage. Organic fertilizers are complementary fertilizers that can maintain soil moisture and fertility, increase the soil water-holding capacity, and increase the amount of water available to plants. The purpose of this study was to determine the effect of compost prepared from banana peel and rotten tomato (10:3) and different watering intervals on the growth of oil palm seedlings at the pre-nursery stage. The experiment was conducted from February 2022 to August 2022 in Kedokan Agung Village, Kedokan Bunder District, and Indramayu Regency. The experiment used a Randomized Block Design consisting of nine treatments and three replicates, with each treatment consisting of two plants. The combination of treatments used compost with intervals of watering the oil palm seedlings. The results showed that the application of 1 kg/plant compost with daily watering resulted in the best growth and significantly affected plant height, trunk circumference, number of leaves, and leaf area. This treatment produced a growth response that was as good as that of plants given inorganic fertilizers. Keywords: compost, organic fertilizer, prenursery, watering interval